Modeling the Spatial Motion of Chromatin and the Whole Process of Gene Transcription (CSIAM Transactions on Life Sciences, 2025)
Biological experiments have verified that chromatin organization has importance influence on gene expression, but the conventional models of gene expression neglect this influence, in particular the effect of enhancer-promoter (E-P) communication on gene expression. Here we first review properties of the classical Rousemodel that is a quite accurate description of chromatin as confirmed by microscopyexperiments. Second, we extend this model to the polymer models with long-rangeinteractions so that they include E-P communications that are typically long-range interactions. We also carry out theoretical analysis for the extended models. Third, weestablish mathematical models for the whole process of gene transcription, which consider connections between upstream chromatin dynamics and downstream promoterkinetics. These connections consider two possible ways of regulation: The one viaE-P encounter probability and the other via E-P spatial distance, both supported bya different experimental measurement. These models lay solid foundations not onlyfor the deep study of gene-expression dynamics but also for the statistical inference ofexperimental data.
Keywords: Gene transcription; polymer model; chromatin dynamics; E-P communication; encounter probability.